Challenges and Adaptations: International Students’ Experiences in Virtual Learning Environments - Lodis Inggridvara Ivada; Angga Widyantara; Aprilita Rizki Wulandari (International Journal of Studies in International Education, 2024)
This paper explores the challenges faced by international students in virtual learning environments, especially those accelerated by the COVID-19 pandemic. Using qualitative interviews and surveys, the study analyzes issues related to technology access, cultural adaptation, and academic engagement. Results highlight both unique struggles and adaptive strategies utilized by students to cope with the demands of online education. The study concludes with recommendations for institutions to better support international students in virtual settings.